Purpose-driven Organizations Management Ideas for a Better World - Rey, Carlos; Bastons, Miquel; Sotok, Phil (Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
"Today, it is impossible to generate trust, reputation or stakeholder commitment without an authentic and coherent purpose. This book illustrates the strategic importance of creating purpose, and underlines how the future of business lies at the intersection of generating profit and creating societal value." -Jaume Giró, Chairman of Corporate Excellence - Centre for Reputation Leadership and CEO, "la Caixa" Banking Foundation "Purpose-driven Organizations is the most comprehensive discussion of purpose available. If you are looking for the cutting edge of academic research, this is your go-to resource." -Claudine Gartenberg, Assistant Professor at Wharton, University of Pennsylvania, USA "This book is the work of one of the pioneers in advocating a deep sense of mission in businesses: the result of over 20 years of consulting with companies across countries and industries, and academic study that has been tirelessly researched" -Alberto Ribera, Senior Lecturer and Director of Executive Coaching, IESE Business School, Spain A higher purpose is not simply about profit. Symbolising the motivations of our actions and efforts, it reflects something much more aspirational and contributes to our global society. This open access book offers novel solutions to ensure employees support a wider organizational meaning whilst guaranteeing that the company benefits from the employee's individual sense of purpose. Advocating a shift from previous models and theories, this book contributes to debate and offers insight for both scholars and practitioners. The chapters bring together academic rigour and practical models to help readers distinguish between the fads and influential strategies. Exploring the development of purpose at each level of business, from strategy and leadership to communication, this book avoids theoretical jargonand provides new approaches to building sustainable purpose-driven organizations.